Muscle activity and accuracy of performance of the smash stroke in badminton with reference to skill and practice - Sakurai, S.; Ohtsuki, T. (Journal of Sports Sciences, 2000)
The aims of this study were to establish the temporal-spatial relationship between muscle activity and the smash stroke of skilled badminton players and to assess performance accuracy using the ellipse of constant distance. We recorded the surface electromyographic (EMG) activity of selected superficial muscles of the stroking arm and shoulder - flexor carpi ulnalis, extensor carpi radialis, triceps brachii (lateral head), biceps brachii and trapezius (upper) - during the badminton smash. In the first part of the study, we examined the characteristics of muscle function and performance accuracy of skilled and unskilled individuals during the badminton smash. Five welltrained badminton players and five students with no experience of badminton were asked to smash a shuttle as hard as they could towards a vertical square target 4 m away, repeating the stroke 30 times.In general, the skilled players showed a more constant time from peak electromyographic amplitude to impact. Immediately after impact, the electromyographic activity of the triceps brachii and flexor carpi radialis of the skilled players decreased; in the unskilled participants, however, it continued until well after impact. The area of the ellipse of constant distance and the off-target distance, which were used as indices of performance accuracy, were smaller for the skilled than for the unskilled participants. In the second part of the study, one skilled and one unskilled participant performed 100 trials a day for 6 days. The time from peak electromyographic amplitude to impact in the extensor carpi radialis and flexor carpi ulnalis was more variable in the unskilled than in the skilled participant even after 6 days of practice, but the proximal muscles of the unskilled participant had a similar pattern of activity to that of the skilled player. Thus, controlling the distal muscles appears to be important for achieving accurate performance of the smash in badminton.